Complement C3 on microglial clusters in multiple sclerosis occur in chronic but not acute disease: Implication for disease pathogenesis. Issue 2 (25th October 2016) - Michailidou, Iliana; Naessens, Daphne M. P.; Hametner, Simon; Guldenaar, Willemijn; Kooi, Evert‐Jan; Geurts, Jeroen J. G.; Baas, Frank; Lassmann, Hans; Ramaglia, Valeria
Abstract : Microglial clusters with C3d deposits are observed in the periplaque of multiple sclerosis (MS) brains and were proposed as early stage of lesion formation. As such they should appear in the brain of MS donors with acute disease but thus far this has not been shown. Using postmortem brain tissue from acute ( n = 10) and chronic ( n = 15) MS cases we investigated whether C3d+ microglial clusters are part of an acute attack against myelinated axons, which could have implications for disease pathogenesis. The specificity of our findings to MS was tested in ischemic stroke cases ( n = 8) with initial or advanced lesions and further analyzed in experimental traumatic brain injury (TBI, n = 26), as both conditions are primarily nondemyelinating but share essential features of neurodegeneration with MS lesions. C3d+ microglial clusters were found in chronic but not acute MS. They were not associated with antibody deposits or terminal complement activation. They were linked to slowly expanding lesions, localized on axons with impaired transport and associated with neuronal C3 production. C3d+ microglial clusters were not specific to MS as they were also found in stroke and experimental TBI. We conclude that C3d+ microglial clusters in MS are not part of an acute attack against myelinated axons. As such it is unlikely that they drive formation of new lesions but could represent a physiological mechanism to remove irreversibly damaged axons in chronic disease. GLIA 2017;65:264–277 Main Points: C3d+ microglial clusters occur in chronic but not acute MS. They are not specific to MS, occur on injured axons and are associated with neuronal C3 production. They likely represent a physiological mechanism to remove irreversibly damaged axons.